Clustering as a strategy for manufacturing performance in the Eastern Cape Automotive industry - Makuwaza, Gwynneth Chandakaita (Rhodes University, Faculty of Commerce, Department of Economics, 2001)
South Africa's current industrial policy focuses on the economy at two levels: a sectoral and spatial level. The former relates to the manner in which industrial policy is concentrating on particular sectors i.e. industrial clusters. This shift in industrial policy from targeting individual industries to an emphasis on industrial clusters, has complemented the change in focus to export promotion under trade policy. Furthermore, there has been increasing recognition of the need to improve industry performance and competitiveness in order to successfully implement export growth. Industry clusters are considered as having the potential to increase manufacturing performance and can provide the basis for sustainable competitive advantage for nations. Consequently the concept of industry clusters was introduced in South Africa in 1997. Because industry clusters are relatively new in South Africa, most of the cluster initiatives in various sectors of the economy are in their early stages of development. Nevertheless, some are already showing signs of potential success in increasing competitiveness in particular sectors. This thesis uses Porter's "diamond" framework apprdach to investigate whether clustering has improved the manufacturing performance of the motor industry in the Eastern Cape. International experience from both developed and developing countries will illustrate the potential of clustering as a powerful strategy in increasing manufacturing performance and consequently competitiveness. Ultimately this should lead to long-term economic development, especially if government adopts clusterbased economic development policies. Information from a survey conducted on both the motor vehicle assemblers and component suppliers is used in this study. The findings reveal that it is mainly the motor vehicle assemblers who have experienced some improvements in manufacturing performance. The components sector on the other hand has not experienced any such improvements. This thesis concludes with the recommendation that it is important to develop cluster policy as a broader and dynamic view of competition. The main emphasis under such policy would be a move from targeting particular industries and providing subsidies towards focusing attention to all clusters in the economy. To effectively apply such a policy requires the repositioning of national, local and provincial government in order to become more involved in regional development issues. Moreover, the various levels of government need to incorporate cluster policy into their competitive strategies.
Keywords: Automobile industry and trade; Automobile industry and trade -- South Africa -- Eastern Cape; Automobile industry and trade -- South Africa -- Eastern Cape -- Performance